2018
DOI: 10.1021/acs.jpclett.8b00583
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of the Simple Arrhenius Law in the Normal Liquid State

Abstract: It is common practice to discuss the temperature effect on molecular dynamics of glass formers above the melting temperature in terms of the Arrhenius law. Using dielectric spectroscopy measurements of dc conductivity and structural relaxation time on the example of the typical glass former propylene carbonate, we provide experimental evidence that this practice is not justified. Our conclusions are supported by employing thermodynamic density scaling and the occurrence of inflection points in isothermal dynam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…A nice resume of the most recent efforts in this fields, showing also new possibilities due to the simultaneous consideration of both the primary relaxation time and DCconductivity is given in ref. [46]. This picture can be supported by the well-known piezoelectricity of PVDF.…”
Section: Discussionmentioning
confidence: 74%
“…A nice resume of the most recent efforts in this fields, showing also new possibilities due to the simultaneous consideration of both the primary relaxation time and DCconductivity is given in ref. [46]. This picture can be supported by the well-known piezoelectricity of PVDF.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, over the years, only a limited number of glass-forming materials have been proven to reveal inflection points experimentally—that is, glycerol, propylene carbonate (PC), Error! Bookmark not defined , 52 2-butyl-1-octanol, 30 protic IL [C 8 HIm][NTf 2 ], 53 and recently [P 666,14 ][BOB]. 54 Casalini and Bair suggested that the origin of the inflection point in PC can be attributed to the pressure dependences of compressibility and the apparent activation energy at a constant volume.…”
Section: Resultsmentioning
confidence: 99%
“…For centuries, supercooled liquids have played a vital role in science, industry, and the day-to-day life of human beings. They develop when their chemical components fail to create crystallization nuclei below the freezing point. Consequently, the formation of supercooled liquids is often related to the manufacturing of glasses (including the molecular ones) via the vitrification process, in which progressive lowering of the temperature results in dramatic slowing down of molecular motions from nanoseconds to hundreds of seconds around the glass-transition temperature ( T g ). ,, This process takes place in both the nonergodic and ergodic dynamic domains of the ultraviscous liquid, which intersect at the crossover temperature T B . , However, well above T g and T B , there is another characteristic point at which intermolecular organization, molecular motion, and transport coefficients (e.g., diffusivity, viscosity) undergo significant changes. These transformations delineate collectively the inflection point which is often referred to as the Arrhenius crossover. …”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 However, well above T g and T B , there is another characteristic point at which intermolecular organization, molecular motion, and transport coefficients (e.g., diffusivity, viscosity) undergo significant changes. 8 10 These transformations delineate collectively the inflection point which is often referred to as the Arrhenius crossover. 11 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation